Management of congential muscular toticollis under one year of age (Journal of Shaheed Suhrawardy Medical College, 2012)
Background and study aim: Torticollis is the postural deformity of head and neck. Congenital Muscular Torticollis (CMT) is a postural deformity of head and neck detected at birth or shortly after birth, primarily resulting from unilateral shortening of Sternocleidomastoid muscle (SCM), In neonates and infants, patient may cure conservatively by physiotherapy but surgery is the treatment of choice for children and adolescents. Here we show our experience regarding management of congenital muscular torticollis with physiotherapy. Patients and Methods: This is an observational descriptive study. Verbal consent from parents was taken. Patients of congenital muscular torticollis with other disease or other congenital anomaly were excluded from study. Twenty patients of congenital muscular torticollis were treated. The cases were enrolled between Nov' 2005 to Oct' 2008 in Bangabandhu Sheikh Mujib Medical University, Gonosasthaya Somaj Vittik Medical College Hospital, ZH Sikder Women's Medical College Hospital, Shaheed Shurawardy Medical College Hospital. Neonates and infants were treated conservatively with physiotherapy and non responsive cases were referred for surgery. Results: Patients age range from 5 days to 1 year of which eleven were females and nine were males. Sternocleidomastoid muscle (SCM) was shortened in all cases (12 on right side and 8 on left side). Of 20 patients 6 neonates, rest 14 infants within 1 year age. Out of 20 neonates and infants 17 were cured conservatively with physiotherapy and rest 3 were referred for surgery. Conclusion: Most of the patient of congenital muscular torticollis can be treated conservatively during infancy. DOI: http://dx.doi.org/10.3329/jssmc.v1i2.12157 Journal of Shaheed Suhrawardy Medical College Vol.1, No.2, December 2009 p.2-5